Problem-solving method and cooperative learning model in nursing education: a single-group pre-post-test study - Chen-Yuan Hsu; Ching-Miao Yang; Sheng-Lei Yan (BMC Nursing)
Abstract Background Prior studies suggest that traditional teaching methods often fail to accommodate students’ individual differences, needs, problem-solving skills, and cooperative learning abilities. This study evaluates the effectiveness of a problem-solving method (PSM) and cooperative learning model (CLM) in nursing education, with a focus on their impact on nursing students’ progress in Paediatric Nursing (PN). Methods A single-group pre-post-test was employed from September 2021 to January 2022. A convenience sample of 51 third-year nursing students enrolled in the PN course at Da-Yeh University, Taiwan, participated in the study. The intervention consisted of an 18-week PN course that was conducted from September 22, 2021 to January 25, 2022 (every Thursday, 13:20 − 16:10). Quantitative questionnaires were administered at three intervals: the first, ninth, and eighteenth weeks of the semester. The research tools included a Basic Information Form (BIF) and the Quantitative Learning Effectiveness Score (QLES). Data were analysed using descriptive statistics, analysis of variance (ANOVA) tests, and linear regression analysis. Results The post-test results at Week 9 revealed that students’ self-perceived PSM, self-perceived problem-solving ability, and self-perceived cooperative learning were significantly greater than their baseline scores (p < 0.05). Similarly, the post-test results at Week 18 indicated that students’ self-perceived problem-solving ability, learning satisfaction, and quantitative learning effectiveness were significantly greater than their baseline scores (p < 0.05). Conclusion This study highlights the benefits of incorporating PSM and CLM into nursing education. The findings suggest that these approaches can enhance learning effectiveness and provide valuable insights into improving PN outcomes for nursing students.